EKSPLORASI ORGANOLOGI DAN INSTRUMENTASI DALAM SENI TRADISI TAMBUR MASYARAKAT SASAK - Galih Suryadmaja; Mukminah; Nurtikawati; Salniwati; Dewi Puspita Ningsih (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This research explores the traditional Tambur art of the Sasak community as a cultural artifact possessing historical, organological, and social significance. The Tambur is not merely regarded as an instrument; it also serves as a symbol of identity and a space for contesting narratives between claims of Balinese heritage and the local Sasak roots. The study indicates that the Tambur has undergone a process of localisation, rendering it an inseparable part of the cultural practices of the Wetu Telu Islamic community, particularly within the context of the Perang Topat ritual. From an organological perspective, the Tambur instrument and its ensemble demonstrate the technological skills of the community in transforming natural materials such as wood, metal, skin, and bamboo into musically meaningful and functional instruments. Its rhythmic and collaborative instrumental structure reflects values of mutual cooperation, spirituality, and a connection to the environment. In a social context, the Tambur serves as a binding medium for the community and a link between generations. It functions as a cultural communication tool that preserves the continuity of tradition amidst the challenges of changing times. Therefore, the preservation of the Tambur should be understood as an effort to maintain the identity and vitality of local culture, which is increasingly threatened by global homogenisation.